Effect of acute and chronic liver diseases on the thyroid function in children - Gihan M. Bebars; Madeha A. Sayed; Lamia Hamdy; Reem A. Abdel Aziz (BMC, 2021)
Abstract Background Thyroid hormones modulate hepatic function through regulation of basal metabolic rate in addition; the liver metabolizes the thyroid hormones and regulates their endocrine effects. Objectives To assess thyroid functions in children with acute and chronic liver diseases. Methods 85 studied children were divided into 4 groups; group 1 (20 children) with acute hepatitis (AH), group 2 (20 children) chronic liver disease1 (CLD1; relatively preserved liver functions including Child-Pugh stage A), group 3 (20 children) chronic liver disease2 (CLD2; includes Child-Pugh stage B or C), group 4 (25 children) controls. All groups were subjected to detailed history, physical examination, Complete blood count, liver, renal function tests, viral markers, and thyroid functions (FT3, FT4, TSH). Results Free T3 levels were lower in children with AH, CLD1 and CLD2. There was significant increase in TSH serum levels in CLD2.In acute hepatitis a negative correlation between serum free T4 and AST (r = -0.991), positive correlation between serum TSH and AST, VLDL, and cholesterol levels (r= 0.503, 0.533 and 0.498). A positive correlation between free T3 levels and prothrombin concentration (r= 0.991). Negative correlations between free T3 levels and PT, serum bilirubin and LDL serum levels in children with CLD2 (r= -0.992) (r= -0.902) and (r= -0.946) Conclusion Acute and chronic liver diseases affect thyroid function in children and is correlated with the disease severity.